EXPERIMENTAL INVESTIGATION OF NICKEL ALUMINIDE (NI3AL) NANOSTRUCTURED COATED ECONOMISER TUBE IN BOILER (International Journal of Engineering Sciences & Management Research, 2016)
Thermal Power Stations all over the world are facing the problem of boiler tube leakage frequently. The consequences of which affects the performance of power plant and huge amount of money loss. Hot corrosion and erosion are recognized as serious problems in coal based power generation plants in India. The maximum number of cause of failure in economizer unit is due to flue gas erosion. The corrosion resistant coatings used conventionally are having some limitations like degradation of the coatings and improper coatings which may lead to pitting corrosion. The nano composite corrosion resistant coating can overcome this problem.Corrosion prevention by the use of nanostructured coatings for separating material from the environment is gaining importance in surface engineering. In this present investigation have attempted to suggest a probable solution for reduction of erosion in economiser zone and its analysis using nano structured coating analysis. In Physical Vapour Deposition (PVD) coating method is used to coated the Economiser tube in boiler. The erosion – corrosion behavior of nanostructured coating on SA210GrA1 steel under actual boiler environment is evaluated. The Nickel Aluminide nanocomposites are characterized using XRD, SEM and EDX.